TWO ARTISTICALLY DECORATED MUSLIM STELES OF THE 14TH CENTURY FROM KUBACHI: ON DATING AND ITS AUTHOR - Mammaev, Misrihan Mamaevic (History, Archeology and Ethnography of the Caucasus, 2022)
The article describes two tombstones of the 14th century in the form of tall trapezoidal stone plates from the largest artistic center of Dagestan – the village of Kubachi. The plates are located in different parts of the medieval Muslim cemetery of “Bidakh Khuppe” (Kubach. – “Cemeteries on the other side”), 1.5-2 km south of the old district of Kubachi, in the lower half of the northern slope of Mount Tsitsila. The steles are examined in comparative terms in order to establish their belonging to the work of one stone-cutting master, as well as to determine the dating of Stele 1, which will allow to answer the question of the process of Islamization of Kubachi. The monuments under consideration are decorated at a high artistic level with late Kufic relief Arabic inscriptions and floral ornaments. The inscriptions were made in the “Blooming Kufi” style by the same stone cutter, calligrapher and ornamentalist, which is proved by the commonality of the forms of both monuments, the technique of their carving, the peculiarities of their decorative finishes, ornamental style, and the unity of compositional decor schemes. The name of the master who made these monuments is unknown. The article reveals certain differences in the decor of the monuments in the style of the letters of the Kufic inscriptions, the details of the ornamental compositions of the central fields, which are clearly associated with the different times of the creation of the steles. Stele 2 is dated 783 AH / 1381-82; Stele 1 has no date. The author of the article believes that Stele 1 is 12-15 years older than Stele 2. In the article, both steles are considered as highly artistic works of Islamic art based on the characteristics of the decorative finish of the letters of the relief Arabic inscriptions of the curb strips, their proportionality, as well as taking into account the expressive floral ornament of the central fields and the framing border epigraphic stripes, the unity and interconnection of the details of the compositions of the central field (Stele 2) and the upper side corners.